Kegagalan Penerapan Economic Statecraft Arab Saudi Terhadap Lebanon Tahun 2016 - Hilfi Biyan Firza (Global Political Studies Journal, 2020)
This paper aims to discuss the failure of economic statecraft carried out by Saudi Arabia against Lebanon in 2016. The difficult economic conditions of Lebanon after the 1975-1990 civil war made Lebanon dependent on foreign aid, one of which was assistance from Saudi Arabia. But in February 2016, Saudi Arabia stopped aid that would initially be used to buy weapons to protect the Lebanese border. The cessation of aid came because of Lebanon's decision not to support an Arab League agreement to condemn Iran over the case of an attack on Saudi diplomatic missions in Tehran. The cessation did not change Lebanon's policy into pro-Saudi but inside Lebanon, the pro-Iranian faction was strengthened by the support of pro-Saudi politicians for pro-Iranian politicians to become the new Lebanese President. This raises the question why Saudi Arabia's economic statecraft efforts to Lebanon have not been successful in influencing Lebanese policy. To know this, this paper will use the political economic statecraft theory from Jean-Marc F. Blanchard and Norrin M. Ripsman. The findings of this paper are the failure of Saudi Arabia's economic statecraft against Lebanon because the level of Lebanese stateness which is at a significant stateness level means that Lebanon has the ability to reject or ignore the economic statecraft.